Dampak Kebakaran Lahan Dan Hutan Terhadap Kesehatan Perempuan Di Kabupaten Pulang Pisau - Sari Marlina; Bambang Supriyono Lautt; Aswin Usup; Revi Sunaryati (EnviroScienteae, 2020)
Forest and land fires are a source of air pollution in Pulang Pisau District. This incident has caused various impacts on women's lives, one of which is a decrease in the level of health. The research objective was to determine the impact of forest and land fires on women's health and the role of women in dealing with forest and land fires. This research was conducted in Pulang Pisau District, Central Kalimantan Province. Sources of data used are primary and secondary data collection. Data analysis in this research was conducted descriptively. Based on the results of the study, it shows an increase in the number of ispa cases followed by the intensity level of the number of forest and land fire incidents. One of the beneficiaries of the forest and land fire incidents are women, children and the elderly. The role and involvement of women so far is only to help prepare foodstuffs and participate in extinguishing fires when forest and land fires occur, but there is still a lack of women's involvement in making prevention and socialization efforts related to the impact of forest and land fires.